Macroscopical Anatomy and Radiographic Study of the Non-Lactating Udder of Adult Local Iraqi Cow (Bos taurus) - Al-Maliki, Salah H.; Atyia, Mahdi A. (The Iraqi Journal of Veterinary Medicine, 2020)
The purpose of this study was to describe some anatomical and radiological features of the non-lactating udder of adult local Iraqi cow. Eight udder of local breed cow clinically appeared healthy and aged between 2-5 years were obtained from a local slaughterhouse located at Baghdad province. Five udders were used for anatomical study and the rest 3 udders were used for the radiological study. The study primed to describe the macroscopic anatomy of the udder and investigate the udder’s normal blood supply using red-colored latex. The mammography method was to describe the duct system of the glandular tissue of the mammary gland which was performed using the iodine compound and barium sulphate as contrast media. The results showed that the udder was located in the inguinal region and covered by pigmented skin with fine hair and composed of four quarters. Each quarter has one teat which was long, cylindrical in shape, opened with one orifice; and internally has longitudinal folds in its mucous membrane. The blood supply of udder by the external pudendal arteries (left and right) branched into cranial and caudal mammary ones. The radiological study showed that the glandular tissue of udder was composed of complex ducal system which included the teat canal (long narrow), teat sinus (spindle-shaped cavity), lactiferous sinus (large round structure), lactiferous ducts, cistern ducts, interlobular duct, intralobular duct and alveoli (round sac like).In conclusion, this study is considered as an important contribution of describing the anatomical features, main blood supply and a pathway of the intraglandular duct system of the non-lactating udder in local cow breed which is necessary for surgical operations in several cases of the udder.